Implementing Waste Sorting as a Sustainable Environmental Awareness Practice for Early Childhood Education - Faizatul Widat; Ika Wulandari; Rizki Fitriandini Wijayanti; Magfirotin Magfirotin (Communautaire: Journal of Community Service, 2025)
This research aims to assess the effectiveness of environmental awareness programs in fostering waste sorting habits among young children at early childhood education. Early childhood education plays a crucial role in instilling sustainable habits, yet there is limited research on how interactive and hands-on learning methods influence environmental consciousness at this stage. The study utilized a qualitative approach with naturalistic observation, supplemented by interviews and direct community partnership program. Data were gathered from both children and teachers through observations, feedback sessions, and participation in waste sorting activities. The findings revealed that children actively engaged in sorting wet and dry waste, demonstrating improved understanding of waste management practices. Teachers reported that the children retained the concepts, showing enthusiasm and applying them outside the classroom. Additionally, parental involvement reinforced the learning, helping to maintain consistent practice at home. The results highlighted the importance of creative, hands-on methods, and teacher involvement in ensuring the sustainability of environmental habits. The study contributes valuable insights into designing future environmental education programs for young children, suggesting that long-term success relies on collaborative efforts from teachers, parents, and the community. Future programs should prioritize interactive, participatory approaches and continuous follow-up to ensure lasting impact.